2023
DOI: 10.12998/wjcc.v11.i3.576
|View full text |Cite
|
Sign up to set email alerts
|

Bowel inflammatory presentations on computed tomography in adult patients with severe aplastic anemia during flared inflammatory episodes

Abstract: BACKGROUND Patients with severe aplastic anemia (SAA) frequently present with inflammatory episodes, and during flared inflammatory episodes, hematopoietic function is further exacerbated. The gastrointestinal tract is the most common site for infectious and inflammatory diseases, and its structural and functional features confer on it the most potent capacity to affect hematopoietic and immune functions. Computed tomography (CT) is a readily accessible approach to provide highly useful informatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…The gastrointestinal tract is an organ that hosts the most abundant lymphatic tissues and microbial community and therefore can provide sufficient activated immune cells and continuously supply exogenous antigens from both pathogenic and commensal microbes to initiate and perpetuate deranged autoimmunity in the context of increased epithelial permeability and gut inflammatory conditions[ 30 - 33 ], leading to autoimmune hematopoietic failure[ 34 - 37 ]. In our retrospective study to explore the inflammatory conditions of SAA patients during inflammatory flare-ups, 5 of 17 recruited patients exhibited imaging abnormalities suggestive of tuberculosis infection, all involving the gastrointestinal tract and suggesting a high frequency of tuberculosis infection in autoimmune hematopoietic failure[ 38 ]. Gut inflammatory conditions in the sustenance of autoimmune responses have been demonstrated by the fact that the onset of an autoimmune disease cannot occur in a germ-free state[ 39 - 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The gastrointestinal tract is an organ that hosts the most abundant lymphatic tissues and microbial community and therefore can provide sufficient activated immune cells and continuously supply exogenous antigens from both pathogenic and commensal microbes to initiate and perpetuate deranged autoimmunity in the context of increased epithelial permeability and gut inflammatory conditions[ 30 - 33 ], leading to autoimmune hematopoietic failure[ 34 - 37 ]. In our retrospective study to explore the inflammatory conditions of SAA patients during inflammatory flare-ups, 5 of 17 recruited patients exhibited imaging abnormalities suggestive of tuberculosis infection, all involving the gastrointestinal tract and suggesting a high frequency of tuberculosis infection in autoimmune hematopoietic failure[ 38 ]. Gut inflammatory conditions in the sustenance of autoimmune responses have been demonstrated by the fact that the onset of an autoimmune disease cannot occur in a germ-free state[ 39 - 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our investigation of inflammatory niches in SAA patients during inflammatory episodes, 5 of 17 recruited patients had imaging abnormalities suggestive of tuberculosis reactivation, all involving the gastrointestinal tract[ 47 ]. Gastrointestinal infections can induce inflammatory lesions in both infected and noninfected segments through induction of gut dysbiosis[ 48 - 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…The contribution of the gut microbiome to sustaining the pathogenesis of graft-versus-host disease after allogeneic hematopoietic stem cell transplantation, a pathogenic mechanism similar to that of AA and frequently used to study AHF pathogenesis in animal models, was reported several decades ago ( 161 ). In our retrospective study, all patients with SAA had imaging abnormalities that reflected the existence of chronic inflammatory lesions and acutely aggravated inflammatory damage in the gastrointestinal tract during inflammatory episodes and exacerbated cytopenia ( 349 ). Similar to non-hematological AIDs ( 156 160 ), growing evidence demonstrates that the gastrointestinal tract is the most common inflammatory nidus that sustains AHF pathogenesis in patients with a background of an inflamed BME ( 89 , 90 ).…”
Section: Particular Attention Should Be Given To Gut Inflammatory Dis...mentioning
confidence: 99%
“…Disseminated tuberculosis ( 368 371 ) or even disseminated BCG vaccination ( 372 ) can induce BM hypoplasia and peripheral cytopenia. The fact that tuberculosis-induced AHF occurs only in disseminated tuberculosis instead of in isolated pulmonary tuberculosis suggests that tuberculosis can infect hematopoietic tissues ( 373 ) or the gastrointestinal tract ( 34 , 35 , 181 , 349 ). Gut involvement and subsequent dysbiosis ( 181 ) likely play more important roles in inducing systemic inflammatory disorders ( 374 , 375 ).…”
Section: Particular Attention Should Be Given To Gut Inflammatory Dis...mentioning
confidence: 99%
See 1 more Smart Citation